ANALYSIS OF LEARNING WITH THE PROBLEM BASED LEARNING MODEL IN HONESTING STUDENTS' KINESTHETIC INTELLIGENCE - Syafillah Rahmadina Devyanti; Agung Setyawan; Mohammad Usman; Moh Rahbini (Citra Dharma Cindekia, 2022)
One type of child intelligence is kinesthetic intelligence. Kinesthetic intelligence is a person's ability to control his movements or manage his body well. The teacher as an educator, has a role to be able to develop children's intelligence through their learning system, including this kinesthetic intelligence. The purpose of this research is to see the applicability of the problem-based learning model in training students' kinesthetic intelligence. The data collection method used is a literature study. The type of data used in this study is secondary data, namely data derived from relevant articles. The data obtained will be compiled, analyzed, and concluded so that conclusions can be drawn regarding the literature study. The application of this problem based learning learning model can lead to increased learning outcomes. This is based on the percentage increase in students who get the Completed interpretation. Because completeness is a benchmark in improving learning outcomes